Antimicrobial Sensitivity of Salmonella Species in Children - A Single-Centered Study - Sijad-ur-Rehman, Haji Gul, Abdul Ahad, Naveed Muhammad, Romana Bibi, Inayat Ullah, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Salmonellae are gram-negative, facultative anaerobic bacteria. Typhoid fever has a non-specific and varied appearance in its early stages. A high-grade fever (>38oC) is the most common presenting sign. Salmonella pathogenicity is primarily determined bythe virulence components it possesses, such as Salmonella pathogenicity islands (SPIs), virulence plasmids, pili, and enterotoxins.The most common drug used was cefixime (66.6%), then ciprofloxacin, and according to a comparable study conducted in Pakistan (33.3%). Cefixime and ceftriaxone had a sensitivity of 60.9% and 65.8%, respectively. In 50.1% of S.typhi isolates, ciprofloxacin sensitivity was observed. Aim: To determine the frequency of the most common salmonella specie and its drug sensitivity in children. Methodology:This descriptive study was conducted in the Department of Pediatrics Bacha Khan Medical Complex Swabi from April 2022 to October 2022 in children with suspected enteric fever. Blood culture reports of suspected patients were sent to the laboratory and reports were followed, before reports arrived patients were started on antibiotics. The sensitivity of drugs was measured by calculating frequency and percentages. Results: This study was conducted on 63 children having blood culture reports presented to us with suspected enteric fever including 25 females and 38 males with a mean age of 6.4±27 years. The most common organism in the blood culture of children presented with enteric fever was salmonella typhi (95.2%). Salmonella paratyphoid species shows 100% sensitivity to co-triaxle, co-trimoxazole and amikacin while 50.8% to azithromycin. Salmonella paratyphi A with 100% sensitivity to amikacin, ampicillin, azithromycin, cefepime, cefoperazone, cefotaxime, co-amoxiclav and colistin. While salmonella typhi were found to be 95.2% with drugs sensitivity amikacin, colistin, fosfomycin, co-trimoxazole, and ertapenem (100%) and ciprofloxacin (73%). Practical implication: by knowing the most common organism and its drug’s sensitivity and resistance, the resistance to antibiotics will be reduced, and targeted antibiotics will be used. Conclusion: Salmonella typhiwas the most common pathogen detected in blood culture (95.2%) with 100%drug sensitivity to amikacin, colistin, fosfomycin, co-trimoxazole, and ertapenem. Keywords: Salmonellatyphi, sensitivity, blood culture, children, enteric fever